PENGEMBANGAN MEDIA E-KOMIK BERBASIS CANVA TERINTEGRASI PROBLEM BASED LEARNING (PBL) PADA PEMBEJALARAN IPAS DI KELAS V SEKOLAH DASAR - Annefa, Putri Salda; Arwin; Hamimah; Gita Rahmi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was driven by low student interest and understanding of abstract Science and Social Studies (IPAS) materials, alongside limited innovative digital learning media in elementary schools. Conventional teacher-centered learning often leaves students struggling to analyze contextual problems. This study aims to develop Canva-based e-comic media integrated with the Problem-Based Learning (PBL) model on the topic "Economic Conditions in My Region" that is valid and practical for Grade V elementary school students. The research follows the Research and Development (R&D) method using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Subjects included expert validators (content, language, and media specialists) and teachers and students from four elementary schools: SDN 05 Mungka, SDN 04 Mungka, SDN 01 Jopang Manganti, and SDN 02 Jopang Manganti. Data were collected through observation, interviews, and validation/practicality questionnaires, then analyzed descriptively. The results indicate that the PBL-integrated e-comic is highly valid based on expert assessments. In the implementation phase, the media was found to be highly practical, with teacher response rates reaching 90%–94% and student responses 86%–93%. In conclusion, the developed e-comic is feasible and practical as an interactive IPAS learning tool. This research implies that the media provides an effective alternative for teachers to enhance student enthusiasm and conceptual understanding through a problem-solving approach. Keywords: E-Comic, Canva, Problem-Based Learning, IPAS